MOTIVASI AMERIKA SERIKAT MENERAPKAN VISA WAIVER PROGRAM (VWP) TERHADAP KOREA SELATAN (2005-2010) - Yannita Khoir; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research analyzes the United State (US) motivation to implement VisaWaiver Program in South Korea at 2008. South Korea has bilateral relationshipwith US since post war world II. South Korea has proposed to become visawaiverprogram participants since 2005. But, both countries signed the VWPMemorandum of Understanding in 2008. This study is a qualitative researchmethod that used nation-state level analysis. The writer used the concept ofnational interest and international cooperation theory. The writer concluded thatUS motivation to apply visa waiver program for South Korea is to increase the USeconomy and international tourism.Keyword: International Cooperation, Visa Waiver Program, National Interest,International tourism.